Interroger les changements de la prison. Des processus de déprise et de reprise institutionnelle - Corinne Rostaing (Tracés, 2009)
This article focuses on the possibilities of change in prison, an institution often described as incapable of change. Judging from our long-term observations in French prisons, this institution is experimenting forms of “detotalization” – in reference to the notion of a “total institution” –, and forms of “decline of the institutional program”, common to other institutions, as well as changes linked to the growing influence of society on prisons, which affects the experience of prisoners. A sociological analysis of these dynamics shows that pressures to make prison a proper institution run counter to security policies which tend to reinforce its use and to open new possibilities for arbitrary power. A concomitant analysis of forms of institutional “withdrawal” and institutional reinforcement will enable us to make sense of these observed changes.